Eco-Literacy Citizenship Education Materials Based on Cultural Value: Research and Development Study at Universitas Negeri Medan - Surya Dharma; Hodriani Hodriani; Halking Halking; Ramsul Nababan (RIRAI Publisher, 2022)
This study aims to develop and validate Eco-Literacy Citizenship Education materials based on cultural value. This teaching material was developed in the Citizenship Education (PKn) subject in Higher Education. The development of teaching materials aims to strengthen citizenship competence, especially students' responsible attitudes towards various global issues such as the environment. The teaching materials developed integrate the principles of environmental awareness and the values ​​of Indonesian local wisdom. The method used is research and development (R&D) by Borg and Gall (1983). Data collection techniques through questionnaires and interviews. The subjects in this study were adjusted to the stages of the research. For introduction, the respondents were 30 Universitas Negeri Medan’s students from the three of study programs, namely Elementary School Teacher Education, Computer Science Engineering Education and Pancasila and Citizenship Education. At the planning stage and initial product development, the subjects of the research were 4 lecturers of Citizenship Education courses. While at the stage of field testing, the subjects of the research were 2 experts on the subject of Citizenship Education. The results of the study indicate that Eco-literacy Citizenship Education Materials based on cultural value are needed to strengthen student citizenship competencies. Expert validation results get an average score of 86.50. These results indicate that the teaching materials developed are categorized as suitable for use in the next test.